2
$\begingroup$

Suppose $(x_n)_{n\in\mathbb{N}}\in\mathbb{R}^{\mathbb{N}}$ satisfies $x_{n+1}=\sqrt{x_n+1}-1$ and that for all $n\in\mathbb{N}$, $x_n\in(-1,0).$

How would I show that the sequence described by this recurrence relation is increasing?

$\endgroup$
  • 1
    $\begingroup$ You have that $(x_{n+1}+1)^2=x_n+1$, but $0< x_{n+1}+1 <1$, so $$x_{n+1}+1>(x_{n+1}+1)^2=x_n+1,$$ then $x_{n+1}>x_n$. $\endgroup$ – guchihe Mar 6 at 1:52
1
$\begingroup$

Letting $y_n = -x_n$, then $x_{n+1} =\sqrt{x_n+1}-1 $ becomes $-y_{n+1} =\sqrt{-y_n+1}-1 $ or $y_{n+1} =1-\sqrt{1-y_n} $.

Therefore $1-y_{n+1} =\sqrt{1-y_n} $.

Letting $z_n = 1-y_n$, this is $z_{n+1} =\sqrt{z_n} $.

If $0 < z_n < 1$, then $0 < z_{n+1} < 1$ and $z_{n+1} \gt z_n$ so $1-y_{n+1} \gt 1-y_n $ so $y_{n+1} \lt y_n$ so $x_{n+1} \gt x_n $.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.